Characterization of South American fur seal (Arctocephalus australis) electrocardiogram - Dassis, Mariela (2019)
The goal of this study was to characterize the Electrocardiogram (ECG) of anesthetized South American Fur Seals (SAFS). Nineteen wild SAFS females were anesthetized with isofluorane at Isla de Lobos (Uruguay). ECG recording was performed at ventral recumbence following standardized procedures. All animals showed normal sinus rhythm. Amplitude and duration of P and T waves, QRS complex, PR interval (PRi), QT interval (QTi) and ST segment (STs) were determined. QT corrected (QTc) was determined in lead II. P wave polarity was consistent among animals (positive in LI, LII, LIII and AVF and negative in AVL and AVR). T wave polarity was consistent among animals only in LI (positive) but without a constant pattern in the others leads. The PRi (0.128±0.009 sec) was highly similar to the allometric prediction (0.130±0.004 sec) for most of mammalian species. Mean eupneic Heart Rate (HR) was 118.95±18.23 bpm (range = 100-160) and also similar to the allometric prediction (111.58±2.79 bpm). The STs were normal in 17 of the SAFS but showed STs depression in 2 animals. Most of the animals (58.9%) had a negative electrical axis. This study constituted the first detailed description of the SAFS ECG.